(untitled) (New York, 2007)
The best minds at Business Week explore ways your company can survive-and thrive-amid the business growth and innovation of China and India. The economic rise of China and India has changed the way the world does business-and today's companies need to step up their game. This in-depth report, edited by a senior writer at Business Week, goes behind the headlines of the new "megamarkets" to explore how your company can stay competitive. With a diverse array of viewpoints, ideas, and forward-thinking strategies, Chindia discusses new avenues businesses can use to embrace change and encourage growth.
Keywords: Trung Quốc; Điều kiện kinh tế